Political Islam: A Comparative Study of Malaysia and Indonesia - Mohammad Hasan Kabir; Halime Nur Mete; Nur Adillah Omar; Sanny Nofrima (KEDJATI Journal of Islamic Civilization, 2024)
This study aims to uncover the history and nuances of political Islam in Malaysia and Indonesia. This research employs a qualitative methodology, specifically library research through content analysis, for its flexibility in systematically analyzing books and journal articles by identifying, coding, and categorizing patterns in the data, thereby providing a comprehensive understanding of their similarities and differences. Malaysia, a Southeast Asian federal monarchy, gained independence in 1957 after a history of colonial occupation. Its multiethnic population includes indigenous tribes and international traders, with Islam as the official religion, though non-Muslims practice freely. Traditional values and the Sultan's role as protector of religion are central to Malay society. Political decisions often weigh ethnic and religious factors. Islam's political role in Malaysia has varied, with prime ministers interpreting its influence differently. Debates range from advocating a full Islamic system to separating religion from politics. Policies have driven Islamization in education, art, music, and clothing, affecting party dynamics between Pan-Malaysian Islamic (PAS) and the United Malays National Organisation (UMNO). UMNO has maintained Malay Muslim support by integrating Islamic sentiments. In Indonesia, a Muslim-majority nation, implementing Islam in politics is complicated by its diverse population. The Pancasila ideology, aligned with Islamic norms, emphasizes monotheism, justice, unity, consultation, and social justice. Despite deep historical roots, integrating Islamic principles in governance requires tolerance of minority views. Political Islam in Indonesia is diverse, with Islamic parties and new Islamist groups influencing governance. Traditional organizations like Nahdlatul Ulama (NU) and Muhammadiyah face competition from groups using media to reshape religious authority.